Pengaruh Sistem Informasi Manajemen dan Bisnis Intelijen Terhadap Informasi Keuangan - Ramadhan, Muhammad Rafi; Firdaus, Kevin Arij; Ilham, Muhammad Quentin; Prasetyo, Adi; Rinjani, Rera; Halizah, Rizky Nur; Mutakin, Saefullah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
Management Information System is an application of information technology in business organizations. This research aims to understand the influence of Business Intelligence Management Information System on financial information. The research method involves literature review by analyzing various books and scientific articles as data sources. Data collection techniques include editing, organizing, and advanced analysis. This research uses a qualitative descriptive approach to explore the role of Management Information System in business competition related to financial information. After the data is collected, descriptive analysis is conducted. The results indicate that the implementation of Business Intelligence Management Information System significantly affects business competition in terms of financial information quality. Businesses that adopt a healthy approach tend to achieve better, accurate, and timely results.